Binospec Software System. (3rd June 2019) - Kansky, Jan; Chilingarian, Igor; Fabricant, Daniel; Matthews, Anne; Moran, Sean; Paegert, Martin; Gibson, J. Duane; Porter, Dallan; Roll, John
Abstract: Binospec is a high-throughput, 370 to 1000 nm, imaging spectrograph that addresses two adjacent 8′ by 15′ fields of view. Binospec was commissioned in late 2017 at the f/5 focus of the 6.5 m MMT and is now available to all MMT observers. Here we describe the Binospec software used for observation planning, instrument control, and data reduction. The software and control systems incorporate a high level of automation to minimize observer workload. Instrument configuration and observation sequencing is implemented using a database-driven approach to maximize observatory efficiency. A web-based interface allows users to define observations, monitor status, and retrieve data products.